(untitled) (Bangladesh Journal of Plant Taxonomy, 2022)
An ethnomedicinal investigation was conducted from July 2019 to June 2020 in Raipura Upazila, Narshingdi district. The main aim of this study was to record, integrate and document all the scattered distributions of traditional healthcare knowledge of medicinal plants. Data collection of ethnomedicinal plants were performed through key informant interviews, field interviews, checklist interviews, Plant interviews, semi - structured interviews and group discussion. A total of 87 medicinal species with 114 formularies to treat 69 ailments have been recorded. These species belong to 49 families. Most frequently used plant species are trees (43%) followed by herbs (31%), shrubs (21%) and climbers (5%). Oral consumption is the main mode of treatment in the study area followed by external application. The reported ailments were classified into 15 disease categories. Maximum plant species were reported to treat diarrhoea and dysentery. The highest Factor informant consensus (Fic) value was found in respiratory category (fever, cold, cough, pneumonia).The most cited species for this category are Ocimum sanctum L., Nigella sativa L. and Jasticia adhatoda L. Cardiovascular disease showed second highest Fic value. The most cited plant species for this category are Terminalia arjuna (Roxb. ex D.C.) Wight & Arn., Tamarindus indica L. and Allium sativum L. In this survey, 8 species scored 100% Fl values for different disease categories. These are Aerva sanguinolenta (L.) Blume, Neolamarckia cadamba (Roxb.) Bosser, Tamarindus indica L., Momordica charantia L., Cocos nucifera L., Ocimum sanctum L., Leucus aspera (Willd.) Link. and Jasticia adhatoda L. Therefore, such plant species could be further analyzed for bioactive constituents that can lead to discovery of new and potential drugs. The study also revealed that the medicinal plants and traditional knowledge in Raipura Upazila are in threatened condition due to different disturbances and some suggestions have been recommended for conservation. Bangladesh J. Plant Taxon. 29(1): 137-156, 2022 (June)